Persepsi Nasabah Terhadap Kualitas Pelayanan yang Berdampak pada Kepuasan Nasabah di PT Permodalan Nasional Madani (Persero) UlaMM Syariah Unit Aceh Barat - Tiara Indah Nirwana; Ivon Jalil; Cut Mega Putri (Indo Publishing, 2026)
This study aims to analyze customers' perceptions of service quality in shaping customer satisfaction at PT Permodalan Nasional Madani (PNM) (Persero) ULaMM Syariah Unit Aceh Barat. The study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving the branch manager, employees, and customers selected using purposive sampling. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that customers generally perceive the service quality provided by PT PNM (Persero) ULaMM Syariah Unit Aceh Barat positively. The tangibles dimension is reflected in adequate facilities and a comfortable service environment. Reliability is demonstrated through accurate and consistent service delivery. Responsiveness is shown by employees' promptness in responding to customers' needs and complaints. Assurance is reflected in employees' competence, courtesy, and ability to build customer trust. Meanwhile, empathy is demonstrated through personal attention and effective communication with customers. These five dimensions collectively shape positive customer perceptions and contribute to customer satisfaction. The study concludes that maintaining and improving service quality is essential to sustaining customer satisfaction and strengthening customer trust in the company.